Autonomic dysfunction, cardio-pulmonary parameters and masked heart failure in non-severe chronic obstructive pulmonary disease - Zheina Cherneva; Radostina Cherneva (Българска кардиология, 2020)
Background: Autonomic dysfunction (AD) and cardio-pulmonary exercise testing (CPET) parameters have been associated with masked heart failure with preserved ejection fraction (HFpEF) in the general population. Their clinical signiﬁcance for masked HFpEF in chronic obstructive pulmonary disease (COPD) is however elusive. Aim: The aim of the study was to determine the prevalence, correlation and clinical signiﬁcance of AD and CPET with masked HFpEF, in non-severe COPD patients, complaining of exertional dyspnea, without clinically overt cardio-vascular (CV) comorbidities (ischaemic heart disease, heart failure, uncontrolled arterial hypertension). Methods and results: We applied CPET and echocardiography in 68 COPD subjects. Echocardiography was performed before CPET and 1-2 minutes after peak exercise. Patients were divided into two groups: patients with and without masked HFpEF. Peak E/e’ – 15 was applied as a cut-off. Chronotropic incompetence (CI) was assumed if both failure to reach the target heart rate (HR) on exercise and diminished heart rate reserve < 80% occurred. Abnormal HR recovery (HRR) was taken if the decline is less than 12 beats within the ﬁrst minute after exercise cessation. Univariate regression showed association between masked HFpEF, HRR, ’VO2, ’VO2 at AT, oxygen pulse and ’VE/’VCO2 slope. The multivariate regression demonstrated HRR as the only independent predictor of masked HFpEF – OR 10.28; 95% CI (3.55-29.80). Conclusion: Abnormal HRR is the only independent predictor of masked HFpEF in non-severe COPD patients. Despite of being associated with masked HFpEF, the lower ’VO2, lower oxygen pulse, higher ’VE/’VCO2 slope and lower exercise load seem to be the consequences, rather than the triggers for it.